The Effect of Alkalization on the Mechanical Properties of Sansevieria Fiber Bio-Composit: Pengaruh Alkali Basa Terhadap Sifat Mekanik Bio-Komposit Serat Sansevieria - Edi Widodo; Ali Akbar; Boy Isma Putra (Academia Open, 2023)
Alkali treatment of natural fibers has a role in removing hemicellulose and lignin layers. This layer prevents the matrix from bonding with the natural fiber cellulose structure. The use of an inappropriate type of alkali will reduce its effectiveness and can even damage the cellulose layer. This study compared the effectiveness of alkaline NaOH, CaOH and KOH in removing lignin and hemicellulose and their ability to maintain cellulose content. The use of the immersion method in alkaline solutions is well controlled. The FTIR characterization test was used to detect functional group changes, the TGV test to detect heat resistance ability, the XRD test to detect structural changes in crystalline and amorphous properties of sansevieria natural fibers. Furthermore, the tensile test to determine the effect of alkaline treatment on changes in mechanical strength Tensile strength. From the test results it was found that the alkaline NaOH gave the best characteristics by detecting the presence of cellulose, tensile strength and the nature of the crystalline atomic structure. Highlights: Effectiveness of Alkali Types: Comparison of NaOH, CaOH, and KOH effectiveness in removing lignin and hemicellulose while preserving cellulose content. Characterization Techniques: FTIR, TGA, and XRD tests used for functional group changes, heat resistance, and structural properties evaluation. NaOH Superiority: Alkaline NaOH treatment demonstrated best results in maintaining cellulose, enhancing tensile strength, and influencing atomic structure. Keywords: Alkali treatment, Natural fibers, Lignin removal, Cellulose preservation, Tensile strength.